A Novel Online System Implementation to Enhance Team-Based Learning at a Medical School - Shaban S; Zafar I; Tariq MI; Magzoub ME (Advances in Medical Education and Practice)
Sami Shaban, Imran Zafar, Mohammad Irfan Tariq, Mohi Eldin Magzoub Department of Medical Education, UAE University, Alain, United Arab EmiratesCorrespondence: Sami Shaban, Department of Medical Education, United Arab Emirates University, POBox 15551, Alain, United Arab Emirates, Tel +971 37137199, Email sami.shaban@uaeu.ac.aeIntroduction: Team-Based Learning (TBL) is an effective learning model utilized in education to address the concerns of student active learning, participation, critical thinking and teamwork. However, faculty members must invest significant time in preparing TBL sessions, creating appropriate material and assessments, preparing paper answer sheets for group tests, and managing the logistics of student groups.Methods: We have designed, developed and implemented a novel TBL online system at our institution by integrating the standard TBL process into a customized IT solution. The objective of this research is to identify important items in the requirements analysis based on sound pedagogy, describe the developed system while highlighting benefits and obstacles faced, and gauge user feedback of the system.Results: The system reduces the burden on faculty by guiding in the preparation of assessments, randomizing students into groups containing students from all academic levels, allowing students to take the individual and group tests efficiently and with instant grading, providing a mechanism for answering questions in the group test in such a way that indicates to students that their answer is incorrect and then allowing them to continue discussion until they reach the correct answer and then grade the question appropriately, allowing facilitator and students to view the progress of each group in the group exams in real-time on a projected screen, and giving an immediate indication on which questions are performing poorly so that immediate discussion and feedback can occur.Conclusion: The system has demonstrated its value in enhancing the learning experience for medical students and has received positive feedback from both facilitators and students. By continuing to innovate, TBL has the potential to play an even greater role in the education and assessment processes of medical professionals.Keywords: team-based learning, TBL, system implementation, medical education